Aedes poilicius DAN PELUANG MENJADI VEKTOR FILARIASIS DI INDONESIA - Sari, Octavia Permata; Rosanti, Tutik Ida; -, Sunaryo; Dwianasari, Lieza; Dwi Sari, Fibi Niken (MANDALA of Health, 2014)
Elephantiasis or Filariasis lymphatic is parasitic infectious disease caused by filarial wormsWuchereriabancrofti, Brugiamalayi, and Brugiatimori,and transmitted by several types of mosquito (Anopheles, Aedes, Culex, MansoniadanArmigeres). This is not a mortal disease but permanent disability that follows brings adverse consequences in both health and socio-economy to either the sufferer or the family. Adult mosquito survey was conducted to figure out the existence of mosquito species identified as the vector of specific disease in an area, to know the bionomics and breeding ground. The above data were of high significance for effective and efficient control.Survey method used was spot survey in July 2013 in Paseh village, Banjarmangu municipality, Banjarnegara Regency. Research materials and utility were aspirator, paper cup, cotton, torchlight, rubber band and mosquito box. Mosquito catching was done all day and night.Evening catch found and identified two Aedespoilicius, the main filariasis vector in Philippine and hasnever been reported as philariasis vector or dengue fever in Indonesia.The similar characteristics of natural environment and demography between Indonesia and Philippine demand awareness of the possibility that this mosquito becomes filariasis vector in Indonesia.Â